POTENTIAL POSSIBILITIES OF SPATIAL DEVELOPMENT OF CITIES AND REGIONS FROM IMPLEMENTATION NON-CONTACT PAYMENT TECHNOLOGIES - O.V. Kolomytseva; І.В. Shevchuk (Економіка та право, 2018)
The article investigates the main trends of cashless payments in Ukraine. The system of cashless payments plays an important role in the development of the economy, as it helps to reduce the share of the shadow sector of the economy, to increase the economic activity of the population, etc. Non-contact payment technologies are mainly used in networks of private struc tures, their integration into the public sector of the economy is taking place at a slow pace. It is proved that technologies of contactless payment create opportunities for spatial development of territories. The high le vel of security of the population by smartphones makes it possible to use NFC technology to make contactless payment for goods and services. The level of their use in Ukraine is analyzed. The directions of practical use of QR codes in economics and management are covered. The intensity of using this technology depends on the increase in the number of owners of smartphones and tablet PCS. It is substantiated that the use of the described methods of contactless payment for fares in urban transport is the first step towards the introduction of an electronic ticket in urban passenger transport. It is suggested to use QR-codes for conducting «QR-questionnaire» in order to assess the quality of service provision in regional and local authorities.